Effect of Chlorophyll Meter and Leaf Colour Chart Based Nitrogen Management on Grain N Uptake for Rice in Iran - VALYNEJAD*, M.; VASEGHI†, S.; FALLAH‡, V.M.; PAZIRA†, E.; FALLAH‡, A.; MOAMENI‡, A. (Asian Journal of Chemistry, 2009)
Over application of N in rice leads to low N recovery efficiency andrisk of NO3 pollution of ground water. The chlorophyll meter also knownas SPAD meter, is a simple, portable diagnostic tool for identifyingcrop N status. We used it to test need based N management approachesfor rice (Oryza sativa L.) in two varieties on a clay loam texture innorthern Iran. The overall objective is to develop optimal N-managementfor Neda and Shirudi. Two varieties were grown under eight treatments.Eight treatments included a zero-N control, chlorophyll meter 35, 37,40, LCC 4 and 5. SPAD readings were taken weekly on the topmostfully expanded leaves. Grain yield, yield attributes, total N uptake andfertilizer - N use efficiency were measured in both varieties. Both LCCand SPAD can be used to improve N management for Neda and Shirudi,but the optimal SPAD threshold for determining the timing of N-applicationwas 35 and 37 for Neda and Shirudi, respectively. LCC treatmentsindicated that N-management based on LCC shade 5 helped avoidover application of N to rice. Neda had higher grain yield than shirudi,but the difference in maximum grain yield among SPAD and LCC treatmentswas insignificant. The two varieties didn't show a clear differencein fertilizer-N use efficiency. It is suggested that when N-managementtechnology such as real time N-management (SPAD and LCC) wereused, would avoid to over application of N fertilizer by rice farmers.